2022
DOI: 10.3390/poultry1020011
|View full text |Cite
|
Sign up to set email alerts
|

Can Early Environmental Enrichment Buffer Stress from Commercial Hatchery Processing in Laying Hens?

Abstract: Under commercial conditions, laying hen chicks are exposed to a range of stressful events immediately after hatch. Here, we studied whether environmental enrichment was able to reduce the stress sensitivity of these chicks. A total of 50 hatchery chicks (HC) and 50 control chicks (CC) were raised in enriched pens (E), while 53 HC + 53 CC were raised in standard non-enriched floor pens (NE). HC weighed less on day one, but there was no effect of hatchery treatment at later ages. HC were more pessimistic in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Latencies to approach the chick/pullet and morph stimuli were intermediate. These results are similar to those obtained in previous studies ( Salmeto et al, 2011 ; Hedlund et al, 2021 , 2022 ), and corroborates that chicks are able to perceive the stimuli differently and adapt their behavior accordingly.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Latencies to approach the chick/pullet and morph stimuli were intermediate. These results are similar to those obtained in previous studies ( Salmeto et al, 2011 ; Hedlund et al, 2021 , 2022 ), and corroborates that chicks are able to perceive the stimuli differently and adapt their behavior accordingly.…”
Section: Discussionsupporting
confidence: 92%
“…To assess whether our cognitive bias test produced results consistent with previous studies employing the same testing paradigm ( Salmeto et al, 2011 ; Hedlund et al, 2021 , 2022 ), we initially conducted an analysis of the first cognitive bias test alone, before range access, on the latency birds took to reach the virtual line. This analysis considered the influence of the stimuli themselves (mirror, chick/pullet, morph, and owl) and the presentation order of stimuli (either chick/pullet or owl during the second trial) as fixed effects.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…To mitigate negative consequences, various attempts have been made to improve the long-term welfare of laying hens, for example, by enriching the rearing environment in order to stimulate a wider range of natural behaviour [ 4 , 9 , 10 ]. Some of the experiments do indeed reveal a positive effect, and there are indications that early enrichment may also buffer some of the stress from commercial hatching by making chickens more resilient against stress later in life [ 11 ], although the results are somewhat ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of bird welfare, research hitherto conducted has identified several factors that can disrupt bird welfare to varying degrees. These occur at all stages of rearing, from the time of hatching [ 5 ] through to beak-correction treatments [ 6 ] and treatment associated with moving the birds between production buildings, or concerning changes to their housing systems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%